(untitled) (Experimental biology, 2020)
Fruit forests of Tien Shan are the centre of origin of several plant species. In this geographical region, many economically valuable species are distributed, such as Malus sieversii (Ledeb.) M. Roem. – Sievers apple tree. The natural populations of M. sieversii of Kazakhstan with a wide range of genetic and phenotypic variations of characters are increasingly subjected to anthropogenic pressure and genetic erosion. It is known that for the effective conservation and rational use of genetic resources, a thorough assessment of the genetic variation that they possess is required. The genetic diversity of 13 clone varieties of M. sieversii of the Dzungarian population of The Main botanical garden’s introduction collection in Almaty (Kazakhstan) and 31 samples from three populations was assessed using 8 polymorphic ISSR markers and iMEC program. To assess the genetic relationships between the studied samples, the expected heterozygosity and average heterozygosity of the samples were calculated. As basic measures, the polymorphism information content (PIC), distinguishing ability (D), effective multiplex ratio (E), marker index MI and resolution (R) were calculated using iMEC. The work revealed a high genetic diversity of clone varieties and samples of the Dzungarian population. As a result of PCA analysis, the studied variety clones and M. sieversii samples from natural populations formed one cloud, which indicates a genetic exchange between these populations. Keywords: Clone-varieties of Sievers apple tree, iMEC program, ISSR-PCR, genetic diversity, Malus sieversii, PCA analysis